Prenatal Gentle Yoga Pada Ibu Hamil Dalam Mengurangi Tingkat Kecemasan dan Stress Menghadapi Persalinan - Sari, Fitria; Aprillia, Yuna Trisuci; Jannah, Miftahul; Mawarni, Endang Siti; Putri, Nafszaqiyah Desma (Universitas Respati Indonesia, 2024)
Feelings of anxiety in pregnancy are relatively common. About 10-15% of all pregnant women experience some level of anxiety or stress during this major transition. Anxiety or anxiety is a feeling of worry, fear that has no clear reason. Partners' problems are a lack of education about complementary yoga services for pregnant women, lack of interest among mothers in pregnancy yoga, anxiety for pregnant women and a lack of certified midwives/therapists to provide complementary yoga services for pregnant women, especially those in rural areas. The solution offered is to increase pregnant women's understanding and knowledge about complementary services for pregnant women's yoga, increasing pregnant women's interest in complementary therapies (pregnant women's yoga). So it can be applied in everyday life. Apart from that, prenatal gentle yoga can relieve the anxiety and stress of pregnant women, so that it can convert anxiety into energy and provide training on complementary therapy (pregnant women's yoga) for pregnant women in the second and third trimesters. The method of implementing the activity is by providing material and practice of prenatal gentle yoga to pregnant women in the second and third trimesters in the Depok area. Next, prenatal yoga material and joint discussions through Focus Group Discussions (FGD).